2007
DOI: 10.1021/jp070855z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of the Activation of Methane by Ta+

Abstract: A guided-ion-beam tandem mass spectrometer is used to study atomic tantalum cations reacting with CH 4 and CD 4 . Like other third-row transition metal ions, W + , Os + , Ir + , and Pt + , the dehydrogenation reaction to form TaCH 2 + + H 2 is exothermic. At higher energies, other products, TaH + , TaCH + , and TaCH 3 + , are observed with TaH + dominating the product spectrum. Modeling of the endothermic cross sections provides the 0 K bond dissociation energies (in eV) of D 0 (Ta + -CH) ) 5.82 ( 0.16 and D 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
73
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 56 publications
(156 reference statements)
15
73
0
4
Order By: Relevance
“…This agostic structure has been found to be characteristic of the early transition metals. 25,28,30,85 Geometrical parameters found here are similar to the structures reported by Di Santo et al 41 and de Almeida and Duarte, 42 who also found a 2 A′ ground state. The CH 2 wagging motion passes through the symmetric 2 A 1 state (a transition state having C 2v symmetry) lying only 0.05 eV higher in energy.…”
Section: ■ Thermochemical and Theoretical Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This agostic structure has been found to be characteristic of the early transition metals. 25,28,30,85 Geometrical parameters found here are similar to the structures reported by Di Santo et al 41 and de Almeida and Duarte, 42 who also found a 2 A′ ground state. The CH 2 wagging motion passes through the symmetric 2 A 1 state (a transition state having C 2v symmetry) lying only 0.05 eV higher in energy.…”
Section: ■ Thermochemical and Theoretical Resultssupporting
confidence: 89%
“…22,23,25,27,28,30,53,69,70,86 In all cases, the difference is attributed to competition with the formation of the metal carbene because of a shared, common intermediate. Because reactions of M + with H 2 produce only one product, no competition exists that may delay the onset of reaction.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…More recently, the details of these reactions, including those metals that cannot activate methane under thermal conditions, were analyzed by combined experimental and theoretical approaches, e.g., for M ϭ Fe (8), Ni (9), Zr (10), Hf (11), Mo (12), Ta (13), W (14), Re (15), Author contributions: D.S. and H.S.…”
mentioning
confidence: 99%
“…In fact, most of the above-mentioned examples of methane activation lead to species that do not react further with methane; exceptions are found among 5d metals (2,3,13,14,19,20). In addition, bare transition-metal ions correspond to the oxidation state (ϩI), which is unusual in condensed-phase chemistry.…”
mentioning
confidence: 99%
“…[11b] W, [14] Ir, [15] und Ta [16] ) durchgeführt. Hçchst interessant war dabei der Befund, dass ein durch Spin-Bahn-Kopplung vermittelter Wechsel von einem High-spin-zu einem Low-spin-Zustand im Zuge der Dehydrierung und vor allem bei der Bildung des zentralen Insertionsintermediates H-M + -CH 3 von entscheidender Bedeutung ist.…”
Section: Dehydrierung Vonunclassified